English English - Badraqa Ali (Jurnal Pijar, 2023)
This research explores which elements of guerrilla marketing that affect advertisement likability among Generation Z consumers in Jabodetabek and Bandung. Despite the growing interest in guerrilla marketing strategies worldwide, there is limited academic research focused specifically on its elements among Generation Z, particularly within the Jabodetabek and Bandung context. This qualitative study aimed to fill this research gap, investigating the role of guerrilla marketing elements in shaping advertisement likability within this demographic group. A triangulated approach was employed for data collection and validation, involving 20 semi-structured, exploratory interviews conducted via Zoom with Generation Z individuals, a comprehensive literature review, and a focus group discussion. Visual elicitation was used during the interviews, utilizing real-world examples of successful guerrilla marketing campaigns to provoke discussion and capture rich, nuanced data. The findings revealed a positive correlation between guerrilla marketing elements and advertisement likability among Jabodetabek and Bandung Generation Z consumers. The results showed a preference for ads that are creative, unexpected, emotionally engaging, aesthetic, and relevant. This research thus provides valuable insights for marketers especially SMEs aiming to connect with Generation Z consumers in Jabodetabek and Bandung. It demonstrates the potential of guerrilla marketing strategies in increasing ad likability and suggests that understanding these tactics could be integral to successfully reaching this influential demographic group. Further research is recommended to validate these findings in other cultural contexts and across different consumer groups.